Investment attractiveness forming of managerial projects - Ostapenko, Tetiana; Arefieva, Olena; Zhyljaev, Igor; Ponomarov, Oleksandr; Hrashchenko, Iryna (Technology audit and production reserves, 2025)
In the modern realities of economic development, investment conditions for entrepreneurial and project activities are of particular importance. The object of this research is the processes of project management that are carried out in the conditions of formation of investment attractiveness. Investment conditions for the formation of management projects become a key factor in the development of project networks both at the national and international levels. One of the most problematic areas is the isolation of investment attractiveness at the macro level of the existence of an economic system for the effective development of management projects. During the study, the following logic of constructing the study was used, which provided for the isolation of the interpretation of investment attractiveness as an economic and theoretical category, which can be defined as a set of external environmental factors, including economic, legal, political, social and cultural factors. These factors are formed at different levels of the economic system: nano-, micro-, meso-, macro-, mega-. The results obtained suggest that in the process of forming investment attractiveness, project networks acquire special importance. They should reflect the availability of project infrastructure and personnel that can initiate, develop and implement projects that relate to a certain industry or region of a particular country. In addition, the results obtained indicate that after determining the theoretical features of project investment attractiveness, approaches to using the category of “investment climate” in the context of project management were outlined. The conditions for forming the investment climate in Ukraine were also assessed, and how investment attractiveness is formed in different countries of the world was indicated. In connection with all the above aspects of forming investment attractiveness, the work provided conditions for increasing the efficiency of implementing management projects. As a result of the research, conclusions were drawn regarding the features of the influence of investment attractiveness factors on increasing the profitability of management projects and on the use of methods for their optimization.